2022
DOI: 10.3389/fgene.2022.892457
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Phenotypic Analysis of the Novel Gaucher Disease Mouse Model With the Partially Humanized Gba1 Gene and F213I Mutation

Abstract: Gaucher disease (GD) is an autosomal recessive lysosomal storage disorder caused by mutations in the GBA1 gene, which produces the glucocerebrosidase (GCase) protein. There are more than 500 mutations reported in GBA1, among which L444P (p.Leu444Pro) and F213I (p.Phe213Ile) are the most common in the Chinese population, while the function of F213I mutation remains elusive. This study aims to establish the GD mouse model of partially humanized Gba1 gene with F213I mutation. In vitro GCase activity assays showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…By Sanger sequencing of the exon 8–11 region of DNA from the patient's peripheral blood, we not only confirmed those two heterozygous mutations but also confirmed that both mutations are located in GBA1 rather than GBAP1 . Many mutations associated with GD have been reported ( 4 , 9 ). There are different types of GBA1 gene mutations and different pathogenic modes, so it is necessary to use appropriate methods to evaluate the pathogenicity of GBA1 gene mutations ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By Sanger sequencing of the exon 8–11 region of DNA from the patient's peripheral blood, we not only confirmed those two heterozygous mutations but also confirmed that both mutations are located in GBA1 rather than GBAP1 . Many mutations associated with GD have been reported ( 4 , 9 ). There are different types of GBA1 gene mutations and different pathogenic modes, so it is necessary to use appropriate methods to evaluate the pathogenicity of GBA1 gene mutations ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…GD is caused by mutations in GBA1 (OMIM #606463), which encodes the lysosomal enzyme glucocerebrosidase (GCase) ( 2 ). To date, more than 500 mutations have been described in the GBA1 gene, including single base changes, splicing alterations, partial and total deletions, insertions, and rearrangements ( 3 , 4 ). GD is categorized into three clinical phenotypes based on the presence or absence of neurological involvement ( 5 ).…”
Section: Introductionmentioning
confidence: 99%